Pteridaie: indicator of the vegetation succession and dynamics in the forests Chablis and Edges in Kahuzi-Biega National Park (Eastern D. R. Congo, Albertine Rift) - Jean De Dieu, Mangambu Mokoso; Honorine, Ntahobavuka Habimana; Pascal, Basinyize Birhashwirwa; Lucien-Gédeon, Lokumu Ilombelombe; Elmar, Robbrecht (International Journal of Biological Research, 2018)
This study was done in different forests Chablis and Edges dominated by the Pteridium aquilinum species in the mountain area of Kahuzi-Biega National Park (PNKB), eastern D.R. Congo, along the Mitumba range, in the Albertine Rift. The main goal of this study is to demonstrate the role of that patch of ferns in the recolonization of degraded areas for the forestry reconstruction and dynamics of different holes in that part of the park. The studied grouping is located at 1531 and 2452m of altitude and on acid soils that root allophatic reactions related to the aptitude of roots and rhizomes of Pteridium aquilinum (L.) Kuhn. The high presence of young Phanerophytes in these sites highlights the position of the grouping in the succession and dynamics of the vegetation. The general aspect of the vegetation is dominantly herbaceous, and presented as a green mosaic in the Pteridaie. The sociological classification shows 8 different eco-sociological groups (apart from non-classified) and Canonical Correspondence Analyses show that the relations between environmental variables and species are significant. The complexity of responses obtained warrants to bring more attention to forests Chablis and Edge diversity for better management and conservation of plant species.
Keywords: Pteridium Aquilinum; Plant Communities; Vegetation Succession; Forest Dynamics; Biological Traits.